HASIL BELAJ AR KETERAMPILAN BERBICARA DENGAN STRATEGI TPS(THINK-PAIR-SHARE ) PESERTA DIDIK SMAN 1 TAMAN SIDOARJ O - Sedhu, Maria Yosefina; Pujosusanto, Ari (LATERNE, 2021)
Speaking is one of the most important skills in German, however speaking skills require a lot of practice. So it is necessary to havelearning strategies that can help students in speaking skills. One strategy that can be used is TPS (Think-Pair-Share TP). The advantages of the TPS (Think- Pair-Share TP) strategy makestudents interact with each other, so that they can practice their speaking skills. The formulation of the problem in this study ishow the learning outcomes of German speaking skills with the TPS (Think-Pair-Share TP) strategy of students at SMA Negeri 1Taman Sidoarjo Class X1 IBB semester 2. The purpose of this study is to describe the learning outcomes of German speaking skillswith a strategy TPS (Think-Pair-Share TP) SMA Negeri 1 Taman Sidoarjo. This type of research is quantitative research. Sourcesof data in this study were students of class X1 IBB SMA Negeri 1 Taman Sidoarjo. While the data of this study were obtained fromthe results of speaking skills tests which were analyzed using the t-test. The results of data analysis show the value of t count18.714> t table 2.042 with a significant level of ? = 0.05. There is an increase in the average value of students’ learning outcomeson reading skills, the average value of the Post Test is greater than the Pre Test. There is a significant difference in the Germanspeaking skills of students at SMA Negeri 1 Taman Sidoarjo class X1 IBB semester 2. Keywor ds: Learning Outcomes, Speaking Skills, Think-Pair-Share Strategy (TPS)